Indicators of clinical performance in monitoring soft tissue sarcoma management: a population-based perspective - Rugge, Massimo; Buja, Alessandra; Tropea, Saveria; Girardi, Giovanni; Cozzolino, Claudia; Zorzi, Manuel; Vecchiato, Antonella; Stefano, Antonella; Del Fiore, Paolo; Brunello, Antonella; Brazzale, Alessandra; Sbaraglia, Marta; et al. (Frontiers in Medicine, 2023)
Soft tissue sarcomas (STS) are rare malignancies which prognosis varies significantly by primary site, histological subtype, and tumor stage. Their low incidence, and the complexity of their clinico-pathological characteristics demand standardized, cancer-tailored diagnostics and therapies managed at high-volume, multidisciplinary care centers. This study evaluates the quality of STS management in north-east Italy (Veneto Region) through a list of ad hoc defined clinical indicators.This population-based study concerns all incident cases of STS in 2018 (214 cases) recorded in the adult population censored by the Veneto's regional Cancer Registry. Based on the international literature, a multidisciplinary working group of experts identified a set of indicators for monitoring the quality of diagnostic, therapeutic, and end-of-life clinical interventions. The quality of care was assessed by comparing the reference thresholds with the indicators' values achieved in clinical practice.Diagnostic procedures showed poor adherence to the thresholds, with a low percentage of histological diagnoses validated by a second opinion. The indicators relating to the surgical treatment of superficial, small, low-grade STS, or of medium, high-grade STS of the head-neck, trunk, or limbs were consistent with the thresholds, while for intermediate, high-grade (large-sized, deep) and retroperitoneal STS they fell significantly below the thresholds.A critical evaluation of the clinical indicators allowed to uncover the procedures needing corrective action. Monitoring clinical care indicators improves cancer care, confirms the importance of managing rare cancers at highly specialized, high-volume centers, and promotes the ethical sustainability of the healthcare system.